Recent Development in Metasurfaces: A Focus on Sensing Applications - Nikolay L. Kazanskiy; Svetlana N. Khonina; Muhammad A. Butt (Nanomaterials, 2022)
One of the fastest-expanding study areas in optics over the past decade has been metasurfaces (MSs). These subwavelength meta-atom-based ultrathin arrays have been developed for a broad range of functions, including lenses, polarization control, holography, coloring, spectroscopy, sensors, and many more. They allow exact control of the many properties of electromagnetic waves. The performance of MSs has dramatically improved because of recent developments in nanofabrication methods, and this concept has developed to the point that it may be used in commercial applications. In this review, a vital topic of sensing has been considered and an up-to-date study has been carried out. Three different kinds of MS absorber sensor formations, all-dielectric, all-metallic, and hybrid configurations, are presented for biochemical sensing applications. We believe that this review paper will provide current knowledge on state-of-the-art sensing devices based on MSs.